Estrategia de fidelización enfocada al producto chip prepago, empresa CNT agencia Orquídeas, ciudad de Guayaquil, 2016 - Burgos Marcillo, Milena Maylín (2017)
This proposal proposes the design of a compendium of loyalty strategies for the CNT Orquídeas Agency based on the results obtained in the study, which addresses the main reason for desertion, of which 43.9% consider that it would do so in case of receiving "poor attention" and with respect to the quality level of the service, where it is evidenced that 26.8% still consider that this one is "deficient"; Therefore, it is determined that prior to the establishment of a loyalty program, a satisfaction strategy must be implemented to increase the retention of CIS Orquídeas - CNT clients. This would be the step towards establishing a closer and lasting relationship with The clients avoiding the loss of the same for the reasons explained above, this will allow this agency to raise its quality level first in care and competitiveness, thus giving a firm step towards the achievement of fully satisfied clients achieving long linkage Term with the company…